Anatomy for Anaesthetists - Ellis, Harold, 1926-; Lawson, Andrew (Medical ethicist) (Chichester, West Sussex, UK : Blackwell Science Ltd., John Wiley & Sons Ltd, 2014)
Of the branches of the sacral plexus.
First published in 1963, Anatomy for Anaesthesists is the definitive anatomy text for anaesthetists in training and remains an invaluable reference for those in practice. The text explores in depth those areas of particular interest to anaesthetists: the respiratory pathway, the heart, the vertebral canal and its contents, the peripheral nerves, the autonomic nervous system, and the cranial nerves, and also includes sections on the anatomy of pain and other zones of anaesthetic interest. This new 9th edition has been fully revised and updated to incorporate developments in regional te.
Part 1. The respiratory pathway, lungs, thoracic wall and diaphragm -- part 2. The heart and great veins of the neck -- part 3. The vertebral canal and its contents -- part 4. The peripheral nerves -- part 5. The autonomic nervous system -- part 6. The cranial nerves -- part 7. Miscellaneous zones of interest -- part 8. The anatomy of pain.
Includes bibliographical references and index.
Online resource; title from front matter PDF (Wiley website, viewed April 22, 2014).
Keywords: Human anatomy; Anesthesiology; Anatomy; Anesthesia; Anatomy; Anesthesia; Human anatomy; MEDICAL -- Anatomy; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Anesthesiology; Human anatomy; Electronic books; Electronic books